Dampak Tiktok: Dekoding Pilihan Pembelihan Fashion Pada Generasi Z Melalui Generasi Strategi Media Sosial dan Inovasi Produk - Arifin, Zainal; Sukaris, Sukaris; Santoso, Rahmat Agus (Jurnal Pekommas, 2024)
This research investigates the impact of TikTok marketing strategies on brand image and purchasing decisions among Generation Z consumers in Indonesia, with a specific focus on the mediating role of product innovation. Utilizing a quantitative approach through an online survey spanning three months, the study collected data from diverse regions without geographical limitations. The sample consisted of 150 Generation Z consumers actively using TikTok and expressing interest in fashion products. Structural Equation Modeling (SEM) analysis using Amos software was employed for data analysis. The results revealed that TikTok marketing strategies significantly influence brand image, supporting Hypothesis 1. Similarly, product innovation has a significant positive effect on brand image, confirming Hypothesis 2. However, TikTok marketing strategies were found not to significantly impact purchasing decisions (Hypothesis 3 rejected), while product innovation significantly influences purchasing decisions among Generation Z consumers (Hypothesis 4 accepted). Additionally, brand image was identified as a significant factor affecting purchasing decisions (Hypothesis 5 accepted). The study concludes that a positive brand image is shaped by effective TikTok marketing and innovative product presentation, influencing the preferences of Generation Z consumers. Despite TikTok marketing's limited impact on purchasing decisions, product innovation plays a crucial role in shaping consumer choices. Practical implications for the fashion industry targeting Generation Z are discussed, emphasizing the need for integrated marketing strategies aligning with innovative product offerings. Recommendations for future research include exploring additional factors and deeper analyses of consumer preferences on the TikTok platform, incorporating demographic and psychographic elements.